Evaluating Marker-Based and Markerless Motion Capture Systems in Reach-to-Grasp Task - Natsakorn Liangsorn; Suradej Tretriluxana (My University, 2024)
This study evaluated the accuracy of marker-based versus markerless motion capture systems in tracking reach-to-grasp movements, using an electromagnetic tracking system as the gold standard. Reach-to-grasp tasks are fundamental activity in daily activities and often affected by neurological conditions like stroke, highlighting the importance of accurate measurement in rehabilitation research. The findings show that the marker-based system consistently outperformed the markerless system, with significantly lower root mean square errors (RMSE) across all axes. The marker-based system achieved an average RMSE of 4.55 millimeters (mm), demonstrating clinical-level accuracy, while the markerless system averaged 23.64 mm, indicating limitations in its ability to track movements with high accuracy.
Keywords: Robot Manipulation and Learning; Human Motion and Animation; Human Pose and Action Recognition